The deepest repetition-free decompositions of nonsingular functions of finite-valued logics - Sokhatsky, F. (Proceedings / International Symposium on Multiple-Valued Logic, 1996)
A superposition is called repetition-free if every variable appears in it at most once. Two terms are said to almost coincide if the second term can be obtained from the first one in a finite number of steps: isotopy change, commutation change and associative change. The main result: every two deepest repetition-free decompositions of a nonsingular function of a finite-valued logics almost coincide. As a corollary we have the corresponding Kuznetaov's results for Boolean functions and Sosinsky's result for functions of three-valued logics.